Correlation Between the Severity Of Chronic Rhinosinusitis and The Degree of Osteitis Based On Computerized Tomography Evaluation - Ardiga Israchmadi; Farah Hendara Ningrum; Nurdopo Baskoro; Anna Mailasari Kusuma Dewi (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: The incidence of chronic rhinosinusitis (CRS) is increasing every year, characterized by inflammation of the nasal and paranasal sinuses mucoperiosteum for more than 12 weeks. The inflammatory process of CRS sometimes spreads to the surrounding bone tissue resulting in osteitis. Computerized tomography scan (CT scan) can assess the degree of mucosal inflammation using the Lund-Mackay score (LMS) while the degree of bone thickening and remodelling are assessed with Global osteitis score (GOS) and Kennedy osteitis score (KOS). AIMS: To evaluate the correlation between CRS severity assessment using LMS and osteitis severity assessment using GOS and KOS METHODS: A retrospective analysis using a cross-sectional design was conducted that included 63 CT scans of the paranasal sinus of CRS patients. The spearman rank test was used to analyze data. RESULTS: Assessment using LMS showed 44% patients were classified as severe, while 29% and 27% patients were classified as moderate and mild respectively. Global osteitis score showed 2% patients were categorized as severe, while 22% and 46% patients were categorized as moderate and mild respectively, and 30% patients were not significant. Based on KOS assessment, it was found that 3% patients were classified as severe, while 38% and 59% patients were classified as moderate mild respectively. There was a significant correlation between CRS severity using LMS and GOS (p 0.000) with rho= 0.951. There was a significant correlation between CRS severity using LMS and KOS (p 0.000) with rho value= 0.452. CONCLUSION: This study shows a significant correlation between CRS severity assessment using LMS and bone thickening and remodelling assessment using GOS and KOS. In comparison with KOS, GOS has stronger relationship with LMS.